2020
DOI: 10.1007/s41207-020-00166-y
|View full text |Cite
|
Sign up to set email alerts
|

“Not seen, not considered”: mapping local perception of environmental risks in the Plain of Mornag and Jebel Ressass (Tunisia)

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Drainage density is crucial for flood risk management, as drainage density discloses the soil's composition and geotechnical properties. It is one of the most important criteria in defining a region's susceptibility to floods [91]. Both models achieved AUC values higher than 0.84 in the ROC investigation, demonstrating their effective performance in predicting flood susceptibility.…”
Section: Discussionmentioning
confidence: 87%
“…Drainage density is crucial for flood risk management, as drainage density discloses the soil's composition and geotechnical properties. It is one of the most important criteria in defining a region's susceptibility to floods [91]. Both models achieved AUC values higher than 0.84 in the ROC investigation, demonstrating their effective performance in predicting flood susceptibility.…”
Section: Discussionmentioning
confidence: 87%
“…The mountains dominate the Mornag plain. Past study by Saqalli et al (2020) revealed that olive trees are cropped intensively and threatened by the expansion of the nearby suburbs of Tunis due to the gap between new peri urban consumption practices in suburban Tunis and rural municipality budgets. Other agriculture-related threat highlights the gap between the vision of a preserved rural area and the agroindustrial reality.…”
Section: Methodsmentioning
confidence: 99%